'L'idée d'une coalition': Derrida, Foucault, and the bumpy coalitions of ACT UP-Paris in Robin Campillo's 120 Battements par minute (2017). (3rd April 2022) - Watson, Eleri Anona
ABSTRACT: In their first newsletter, ACT UP-Paris reject the concept of an 'AIDS community'. Recognising 'community' as tantamount to homogenisation, ACT UP-Paris declare themselves a 'coalition'. This implies resistance to identarian cohesion. Instead, they claim to adopt a politics of identification that embraces diversity and dispersion. This philosophy represents an ACT UP-Paris 'way of life'. This article mobilises archival materials alongside Robin Campillo's 120 Battements par minute (2017) to examine the nature and scope of this coalitional way of life. Engaging in a new, queer reading of Jacques Derrida's relational politics, I contend that Derrida articulates a 'bumpy' relationship between self and other. The bump forges a momentary connection at a certain point, a distancing at another: an identification and dis-identification—respecting the other in its otherness. Bumping articulates not a unified identity but an identification politics of being-together in difference. This epitomises ACT UP-Paris' way of life. The risks and joys of this way of life are brought into focus by 120 BPM. Examining the film's depiction of activism's relational bumps, irreconciled community and campy bumps, I conclude that ACT UP-Paris' way of life is neither utopian nor dystopian, but rather a politic of radical hope for relationality without reconciliation.